PENERAPAN BUILDING INFORMATION MODELING (BIM) PADA PERENCANAAN ULANG STRUKTUR ATAS GEDUNG TIMUR PONDOK AL FITHRAH SURABAYA - M. Hadziq Azhari; Nawir Rasidi; Deni Putra Arystianto (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2025)
Al Fithrah East Wing Building, Surabaya is a building that doesn’t used advanced tech such BIM. They were use BIM tools like AutoCAD were used for planning, but they were time-consuming and lacked integration, resulting in increased costs, resource allocation, and project duration. Consequently, this study aims to compare BIM with traditional methods. The researchers employed interviews, surveys and a case study to assess the performance of BIM. By comparing the efficiency of conventional methods with the BIM concept in project planning for a building with differences in method and structures will impact on budget planning in this case. The redesign process start from pre-eliminary design to determine the dimensions of colomn, beam, and slab. Calculating loads including dead loads, live loads, roof load, wind load, rain load, and earthquake load. Do trial and error to analyze the structure then collaborate model with other BIM application to calculate the Quantity and create cost estimation.